A π-conjugated dual-functional redox mediator facilitates the construction of dendrite-free lithium–oxygen batteries. Issue 2 (16th December 2022) - Li, Chu-Yue; Wu, Min-Sheng; Chen, Wei-Rong; Wang, Qian-Yan; Rong, Yuan-Jia; Zhang, Xiao-Ping
Abstract : We present a π-conjugated TBMPSiBr as a dual-functional redox mediator, which can concurrently dissolve Br − /Br3 − and in situ produce an organic–inorganic hybrid SEI on the lithium anode to construct dendrite free and long cycle life Li–O2 batteries. Abstract : Lithium metal with a high capacity of 3860 mA h g −1 is regarded as the "holy grail" of rechargeable batteries. However, the dendrite growth and high overpotential restrain its practical application. Herein, a novel phenyl bromide silane tert -butylmethoxyphenylsilyl bromide (TBMPSiBr) is applied as an organic–inorganic hybrid solid electrolyte interphase-forming agent and a redox mediator for lithium–oxygen batteries. Based on π-conjugation, the organic components can improve the flexibility of the SEI layer to accommodate volume changes of the lithium anode during cycling. And the inorganic silane groups present can chemically form Li–O–Si bonds with the lithium anode, thus ensuring the toughness and high ionic conductivity of the formed SEI layer. Combined with the dual properties of the hybrid SEI layer and the simultaneously dissociated redox couple Br3 − /Br −, the TBMPSiBr-containing lithium–oxygen batteries can stably cycle 220 times with a low overpotential, significantly enhancing the cycling stability.